Upaya Penguatan Budaya Literasi Membaca Siswa Pada Pembelajaran Bahasa Indonesia Di SD Cibeunteur - Asep Nurjen; Asep Sahrul Gunawan (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
Reading literacy culture in elementary schools is one of the fundamental foundations for shaping students' critical thinking skills, language competence, and learning achievements. This study aims to describe and analyze the efforts to strengthen students' reading literacy culture in Bahasa Indonesia learning at SD Cibeunteur. This research employed a qualitative approach with a descriptive qualitative design. Data were collected through in-depth interviews with classroom teachers and the school principal, non-participatory classroom observation, and documentation study of school literacy programs and learning plans. The findings reveal that SD Cibeunteur has implemented various strategic efforts, including the Fifteen Minutes Reading program conducted before learning activities, the development of a literacy corner in each classroom, the use of diverse and contextually relevant reading materials, as well as reading comprehension activities integrated into Bahasa Indonesia learning. Teachers play a central role as reading motivation models and facilitators in cultivating positive reading habits among students. However, challenges remain, including students' limited reading interest, insufficient availability of reading materials, and the lack of parental involvement in fostering a reading culture at home. These findings underscore the need for holistic and sustainable collaboration among teachers, parents, and school institutions to effectively strengthen reading literacy culture in elementary education.